Analisis Kinerja Keuangan Mengenai Tingkat Kesehatan Bank Dengan Menggunakan Metode Camel ( Studi Kasus Pada Pt. Bank Bukopin Tbk Periode 2010-2012) - FARISKA PANGESTUTI, AVIANA, Dra. Chuzaimah, MM (2017)
Measuring the level of health of tha bank is very important for bank. Not only to the bank it's selft, but also important for the public using bank services, as well as the Indonesian bank manager and supervisor of banks as an arm of the government. To measure the health of banks, may be using the CAMEL. In this study has the formulation of the problem is "How the bank's financial performance in the years 2010-2012 with use CAMEL method?" This research uses secondary data, using the existing financial statements on a bank's balance sheet, statement credit growth, income statement, statement of capital adequancy, etc. besed on the results of the study indicated that for the years 2010 had a value of 86,81 for the year 2011 amounted to 89,51 and in 2012 amounted to 89,22. So until the period 2010-2012 have healty predicate.